The Effect of Regional Original Revenue and Capital Expenditure on the Financial Performance of Local Governments in North Sumatra Province - Siti Hajar; Agus Tripriyono; Ayu Kurnia Sari (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of Local Own-Source Revenue (PAD) and Capital Expenditure on the financial performance of the regional government in North Sumatra Province. The research employs a quantitative approach using secondary data obtained from regional government financial reports and related statistical publications for the 2019–2023 period. Multiple linear regression is applied, supported by classical assumption tests, partial significance testing (t-test), simultaneous significance testing (F-test), and the coefficient of determination. The results show that, partially, PAD has no significant effect on financial performance (Sig. 0.411 > 0.05), while Capital Expenditure has a positive and significant effect (Sig. 0.031 < 0.05). Simultaneously, PAD and Capital Expenditure significantly affect financial performance (Sig. 0.002 < 0.05). The Adjusted R Square of 0.453 indicates that approximately 45.3% of the variation in financial performance can be explained by PAD and Capital Expenditure, while the remaining portion is influenced by other factors outside the model. These findings suggest that improvements in regional financial performance are more consistently driven by productive spending—particularly capital expenditure—than by increases in PAD alone. Therefore, the regional government should strengthen PAD management and allocate capital expenditure effectively and efficiently to enhance financial performance.